Recensione a Francesco Della Puppa, Giuliana Sanò (eds.), Stuck and Exploited. Refugees and Asylum Seekers in Italy Between Exclusion, Discrimination and Struggles, Venezia, Edizioni Ca’ Foscari, 2021 - Zadra, Franca (Antropologia Pubblica, 2024)